Postmortem 9.4-T MRI for Fetuses With Congenital Heart Defects Diagnosed in the First Trimester - Tang, Huirong; Zhang, Yan; Dai, Chenyan; Ru, Tong; Li, Jie; Chen, Jieyu; Zhang, Bing; Zhou, Kefeng; Lv, Pin; Liu, Renyuan; Zhou, Qing; Zheng, Mingming (Frontiers in Cardiovascular Medicine, 2022)
Objective: To evaluate the feasibility of 9.4-T postmortem magnetic resonance imaging (pm-MRI) for assessment of major congenital heart defects (CHD) cases terminated in the early stage of gestation. Methods: Fetuses with CHD detected by the detailed first-trimester ultrasound scan and terminated before 18 gestational weeks were recruited between January 2018 and June 2020. All fetuses were offered 9.4-T pm-MRI examinations and those terminated over 13+6 weeks were offered conventional autopsies simultaneously. Findings of pm-MRI were compared with those of conventional autopsy and prenatal ultrasound. Results: A total of 19 fetuses with major CHD were analyzed, including 6 cases of atrioventricular septal defect, 5 cases of Tetralogy of Fallot, 3 cases of hypoplastic left heart syndrome, 1 cases of tricuspid atresia, 1 case of transposition of the great arteries, 1 case of severe tricuspid regurgitation and 2 cases of complex CHD. Pm-MRI had concordant findings in 73.7% (14/19) cases, discordant findings in 15.8% (3/19) cases and additional findings in 10.5% (2/19) cases when compared with prenatal ultrasound. Pm-MRI findings were concordant with autopsy in all 8 CHD cases terminated over 13+6 weeks. Conclusions: It is feasible to exhibit the structure of fetal heart terminated in the first trimester clearly on 9.4-T pm-MRI with optimized scanning protocol. High-field pm-MRI could provide medical imaging information of CHD for those terminated in early stage of gestation, especially for those limited by conventional autopsy.